Philodryas trilineata (Argentinean mousehole snake). Diet - Minoli, Ignacio (2013)
Philodryas trilineata is a large (maximum length = 200 cm) species endemic to the Monte biogeographic region in western Argentina (Giraudo and Scrocchi 2002. Smithson. Herpetol. Inform. Serv. 132: 1-53). The diet of P. trilineata is known to include birds, mammals, lizards, and other snakes; some individuals are known to hunt domestic fowl or rabbits (Cei 1993. Reptiles del Noroeste, Nordeste y Este de la Argentina. Herpetofauna de las Selvas Subtropicales, Puna y Pampas. Mus. Reg. Sci. Nat. Torino. 945 pp.; Laspiur et al. 2012. Herpetol. Rev. 432151-152).